IMPLEMENTASI KEBIJAKAN PNPK TATA LAKSANA THALASSEMIA DI KABUPATEN SUBANG - Wanti Dewanti; Ira Irawati; Mas Halimah (Yogyakarta State University, 2019)
The increase of patients suffering Thalassemia especially in Subang district pushed the estabilishment of the organization named POPTI. The objective of this study is to analyse the role of POPTI in implementing handling policy PNPK of Thalassemia patients. The research method used is qualitative with conducting semi structured interview, observation, and documentation research. The result of this research shows that the role of POPTI is significant important in handling Thalassemia patients, yet the role has not fully gone well. There is still lack of coordination and communication between members and related agencies. This is the reason for implementing the handling policy of Thalassemia patients in Subang district, which hasn’t been optimal. Therefore, it is necessary to improve the system and awareness of chairman and members to coordinate and collaborate for handling Thalassemia patients in Subang district.